Balancing the needs of individuals and services in cancer treatment for people with dementia: A focused ethnographic study. (September 2021) - Griffiths, Alys Wyn; Ashley, Laura; Kelley, Rachael; Cowdell, Fiona; Collinson, Michelle; Mason, Ellen; Inman, Hayley; Henry, Ann; Farrin, Amanda; Surr, Claire
Abstract: Background: Managing multiple conditions is difficult for patients and their families, increasing complexity in care. Two of the most common long-term conditions, cancer and dementia, both disproportionately affect older adults. However, little is known about the needs and experiences of those living with both conditions, which could inform practice in the area. Objectives: This focused ethnographic study sought to understand how oncology services balance the unique and complex needs of these patients with those of the service more widely. Design: Focused ethnography. Setting: Two National Health Service hospital trusts. Participants: Seventeen people with dementia and cancer, 22 relatives and 19 staff members participated. Methods: Participant observation, informal conversations, semi-structured interviews, and medical notes review. Results: Improved satisfaction and outcomes of care were reported when staff were delivering person-centred care. Staff tried to balance the need for personalised and flexible support for individuals with dementia with managing targets and processes of cancer care and treatment. The importance of continuity of people, places, and processes was consistently highlighted. Conclusion: Navigating and managing the delicate balance between the needs of the individual and the needs of services more widely was difficult for both staff and patients. Improved awareness, identification and documentation of dementia would help to ensure that staff are aware of any specific patient needs. Consistency in staffing and appointment locations should develop familiarity and routine for people with dementia.